Spasmophilia Grade IV in Pregnancy: Diagnosis and Conservative Management of a Rare Neuromuscular Disorder of Calcium Dysregulation - A Case Report - Muhammad Satria Erlangga Sinum; Nuswil Bernolian; Abarham Martadiansyah; Hasnawi Haddani (Media of Health Research, 2026)
Spasmophilia is an uncommon neurovegetative disorder characterized by tissue-level calcium dysregulation and neuromuscular hyperexcitability. Its occurrence in pregnancy is rarely reported, and the physiological remodeling of calcium and magnesium homeostasis during gestation poses distinctive diagnostic and therapeutic challenges. Case Presentation. A 26-year-old primigravida at 36–37 weeks of gestation presented with a history of intermittent stiffness and cramping of the hands and feet that had been diagnosed electrophysiologically as grade IV spasmophilia prior to conception. Involuntary movements had abated during pregnancy. Physical examination revealed positive Chvostek and Trousseau signs; a nerve conduction study demonstrated the repetitive multiplet discharges characteristic of grade IV disease. Laboratory evaluation showed mild anemia (hemoglobin 6 g/dL) with calcium and magnesium within the lower reference ranges. Management and Outcome. The patient was managed conservatively with oral calcium carbonate, folic acid, ferrous sulfate, and neurotropic B vitamins, along with non-pharmacological measures, while avoiding benzodiazepine muscle relaxants, which are contraindicated in pregnancy. She delivered a healthy female neonate (3,175 g, Apgar 8/9) at term without neuromuscular complications. Spasmophilia in pregnancy can be diagnosed through a structured integration of clinical signs, electrophysiological assessment, and electrolyte assessment, and is amenable to safe conservative management centered on calcium supplementation and avoidance of teratogenic relaxants.